Morocco : Request for an Arrangement Under the Precautionary and Liquidity Line and Cancellation of the Current Arrangement-Press Release; Staff Report; and Statement by the Executive Director for Morocco. (IMF Staff Country Reports; Country Report ;, 2016)
This paper discusses Morocco's request for an arrangement under the Precautionary and Liquidity Line (PLL) and cancellation of the current arrangement. Morocco's economic fundamentals and policy frameworks are sound. The country is implementing sound policies and remains committed to maintaining such policies in the future. The IMF staff assesses that Morocco performs strongly in four of the five areas of PLL qualification, does not substantially underperform in the fiscal area, and does not face any of the circumstances under which the IMF might no longer approve a PLL arrangement. The IMF staff recommends the approval of the authorities' request.